Age-Dependent Progression in Lung Pathophysiology can be Prevented by Restoring Fatty Acid and Ceramide Imbalance in Cystic Fibrosis - Youssef, Mina; De Sanctis, Juan B; Shah, Juhi; Dumut, Daciana Catalina; Hajduch, Marian; Petrof, Basil J; Radzioch, Danuta (Lung, 2020)
PURPOSE: Cystic fibrosis (CF) is a progressive disease which causes a continuous decline in lung capacity with age. Our study aimed to investigate the age-dependent deterioration in lung function and the effects of treatment with Fenretinide formulation (LAU-7b) in Cftr knockout (KO) mice. METHODS: Non-invasive whole-body plethysmography (WBP) was done to measure the baseline lung functions of KO and wild-type (WT) mice at the ages of 2 and 4 months. Mice were then treated for 21 days with PBS or 10 mg/kg/day LAU-7b initiated at 4 and 7 months. Standard airway resistance measurements, haematoxylin and eosin staining, and analysis of lipids, and markers of oxidation were performed. RESULTS: The 4- and 7-month-old KO mice had significantly higher lung enhanced pause (Penh) and resistance values than age-matched WT mice and 2-month-old KO mice. Likewise, analysis of ceramides showed that PBS-treated mice had higher levels of long-chain ceramides (LCCs; C14-C18) and lower levels of very-long-chain ceramides (VLCCs; C24-C26) compared to LAU-7b-treated mice. Cftr KO mice displayed markedly greater inflammatory cell infiltration and epithelial hyperplasia at the ages of 2, 4, and 7 months compared to WT. LAU-7b treatment significantly diminished this cellular infiltration and epithelial hyperplasia compared to PBS-treated mice. CONCLUSION: Our results demonstrate a progressive age-dependent decline in lung function in Cftr KO mice. Treatment with LAU-7b corrects the lipid imbalance observed in the aging KO and WT mice and, more importantly, inhibits the age-dependent deterioration in lung physiology and histopathology.
Keywords: Aging; Disease Progression; ceramidy; progrese nemoci; Disease Models, Animal; Fatty Acids; Ceramides; LAU-7b; rezistence dýchacích cest; Chromatography, High Pressure Liquid; Mice; Fatty acids; vysokoúčinná kapalinová chromatografie; Ceramide imbalance; myši knockoutované; Cystic Fibrosis; Cystic fibrosis; věkové faktory; stárnutí; pletysmografie; modely nemocí na zvířatech; zvířata; plíce; Mice, Knockout; Plethysmography; myši; mastné kyseliny; Age Factors; Airway Resistance; Cftr knockout mice; Lung; Airways inflammation; cystická fibróza; Animals